1994
DOI: 10.1128/jvi.68.3.1586-1596.1994
|View full text |Cite
|
Sign up to set email alerts
|

Genomic cloning and complete sequence analysis of a highly divergent African human immunodeficiency virus isolate

Abstract: Analysis of the complete sequence of a human immunodeficiency virus (HIV) isolate (Ant70) obtained from a Cameroonian patient indicates that this virus is the most divergent strain within the HIV-1 family hitherto described. Comparison of the Pol protein, usually highly conserved within the HIV-1 family, shows only about 73% similarity with the HIVmm isolate, whereas for the more variable proteins such as envelope, similarities of 50% or lower are found. The principal neutralizing determinant (V3 loop) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(58 citation statements)
references
References 68 publications
1
57
0
Order By: Relevance
“…Decreased or not detectable antibody reactivity related to a distant HIV-1 variant has been described [van den Haesevelde, 1994;Simon et al, 1998]. The nearly complete sequencing of the genome of HIV-G829 showed that this virus was a recombinant, mostly subtype A, whose nef gene related to subtype G, the most commonly prevalent genotypes in this area [Davies et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased or not detectable antibody reactivity related to a distant HIV-1 variant has been described [van den Haesevelde, 1994;Simon et al, 1998]. The nearly complete sequencing of the genome of HIV-G829 showed that this virus was a recombinant, mostly subtype A, whose nef gene related to subtype G, the most commonly prevalent genotypes in this area [Davies et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…The three isolates belong to different genetic groups. MN and VI525 belong to HIV-1 Group M, and CA9 belongs to HIV-1 Group O. Sequence analysis has shown that Group M and Group O show on average only 53-62% similarity in the nucleic acid sequence and 50% similarity in the amino acid sequence of env [Gü rtler et al, 1994;Vanden Haesevelde et al, 1994]. These data suggest that if a serum is able to neutralize three viruses belonging to genotypes with very low homology, that serum recognizes epitope(s) conserved among these divergent isolates and very likely also on other, less divergent isolates.…”
Section: Discussionmentioning
confidence: 99%
“…ANT70 was classified as a Group O isolate based on the full genome sequence [Vanden Haesevelde et al, 1994].…”
Section: Phylogenetic Characterization Of Hiv-1 Virus Isolatesmentioning
confidence: 99%
“…These viruses are characterized by extensive alteration in their nucleotide sequence [Wong-Staal et al, 1995]. As a consequence, HIV-1 isolates have been subdivided into group M with at least eight genetic subtypes (A through H) [Myers et al, 1993] and group O [De Leys et al, 1990;Gurtler et al, 1994;Vanden Haesevelde et al, 1994]. HIV-1 group O isolates are highly divergent from group M isolates, differing by about 50-60% in the env gene Vanden Haesevelde et al, 1994].…”
Section: Introductionmentioning
confidence: 99%